Sustainable Water Farming with Aquaponics - Nur Aniss Suraya Ibrahim; Saputeri Saifuddin; Kirtiga Nadarajan; Nornajihah Mohammad Yazid; Nor Baizura Hamid (Multidisciplinary Applied Research and Innovation, 2026)
Aquaponics is an integrated agriculture system that brings aquaculture to the system and fish production together with hydroponics as the plant culture approach. Conventional agriculture meets great challenges, such as over-utilization of water, evaporation, and runoff, with over fertilization with chemical fertilizers that degrade soil, pollute water, and diminish biodiversity. Opposite to making agriculture costly and resource-intensive, these form processes toward an environmental conundrum that demands alternative solutions. Aquaponics tries to resolve such a dilemma by providing a sustainable food production system that conserves water, reduces chemical use, and supports plant growth and fish production in a closed-loop system. This project is an attempt to design and construct an aquaponic system that will monitor water quality parameters and plant growth for 12 weeks. The system consisted of a fish tank and a planting area, with water continuously circulated between them so that nutrients will be recycled and balance maintained. Water testing showed that the system maintained an average pH of 6.65, average temperature of 22.47˚C, and average ammonia concentration of 0.47 mg/L. The average value for dissolved oxygen amounted to 6.00 mg/L and BOD value at 1.71 mg/L, both suitable for the sustenance of aquatic and plant life. Tracking of lettuce development on a weekly basis showed an average growth of 16.86 cm throughout the period. This study holds significance in proving aquaponics as one of the impressively cheap, water-savvy, and environmentally friendly ways of farming. Water savings can be up to 90% compared to conventional methods, growing organic veggies and fishes without using chemical fertilizers, preventing agricultural runoff, and being suitable for urban and small-scale applications. Thus, overall, the study has proven small-scale aquaponics to be a feasible and sustainable method of growing food, thereby bearing potential for commercial scaling in aid of food security and environmental conservation.